Bidirectional plant‐mediated interactions between rhizobacteria and shoot‐feeding herbivorous insects: a community ecology perspective. (23rd October 2020) - Friman, Julia; Pineda, Ana; van Loon, Joop J.A.; Dicke, Marcel
Abstract : Plants interact with various organisms, aboveground as well as belowground. Such interactions result in changes in plant traits with consequences for members of the plant‐associated community at different trophic levels. Research thus far focussed on interactions of plants with individual species. However, studying such interactions in a community context is needed to gain a better understanding. Members of the aboveground insect community induce defences that systemically influence plant interactions with herbivorous as well as carnivorous insects. Plant roots are associated with a community of plant‐growth promoting rhizobacteria (PGPR). This PGPR community modulates insect‐induced defences of plants. Thus, PGPR and insects interact indirectly via plant‐mediated interactions. Such plant‐mediated interactions between belowground PGPR and aboveground insects have usually been addressed unidirectionally from belowground to aboveground. Here, we take a bidirectional approach to these cross‐compartment plant‐mediated interactions. Recent studies show that upon aboveground attack by insect herbivores, plants may recruit rhizobacteria that enhance plant defence against the attackers. This rearranging of the PGPR community in the rhizosphere has consequences for members of the aboveground insect community. This review focusses on the bidirectional nature of plant‐mediated interactions between the PGPR and insect communities associated with plants, including (a) effects of beneficial rhizobacteria via modification of plant defence traits on insects and (b) effects of plant defence against insects on the PGPR community in the rhizosphere. We discuss how such knowledge can be used in the development of sustainable crop‐protection strategies. Abstract : Plants interact with a community of plant‐growth‐promoting rhizobacteria (PGPR) and an aboveground community of insects. Plant‐mediated interactions between belowground PGPR and aboveground insects have usually been addressed unidirectionally from belowground to aboveground. This review takes a bidirectional approach to these cross‐compartment plant‐mediated interactions. Aboveground insect herbivory may influence root exudates, altering PGPR community processes, thereby modifying plant defence against aboveground herbivores. Understanding such bidirectional processes may provide opportunities for crop protection.